Understanding oxidative addition in organometallics: a closer look. Issue 17 (26th January 2022) - Behera, Nabakrushna; Sethi, Sipun
Abstract: Understanding oxidative addition is crucial for the prediction of chemical reactivity and to explain mechanisms of reactions that are catalyzed by organometallic complexes. Despite its importance in the organic and inorganic curriculums, students frequently encounter difficulties with this concept. The goal of this study is to present oxidative addition by highlighting the history, fundamental concept, mechanism and scope. Relevance to current applications is briefly described. The majority of results discussed in this review have been derived from recent decades to ensure completeness. Moreover, classical oxidative addition of single-metal two-electron reaction which was not observed earlier for f-block elements due to their irreversible one- or multi-electron redox reactions, has recently been explored for a uranium complex and is presented. Graphical Abstract: UF0001